Characteristics and Predictors of Abstinence Among Smokers of a Smoking Cessation Clinic in Hunan China - Hu, Yina; Xie, Jianghua; Chang, Xiaochang; Chen, Jianhua; Wang, Wei; Zhang, Lemeng; Zhong, Rui; Chen, Ouying; Yu, Xinhua; Zou, Yanhui (Frontiers in Public Health, 2021)
Abstract Background: More than 300 million smokers make China the largest cigarette consumer globally, which is a huge economic burden. Smoking cessation (SC) clinics can offer counseling and follow-up services. The operational experience of SC clinics in China needs to be summarized and improved based on research evidence. Purpose: The objectives of this study were to describe quit rates among attendees of SC clinics in Hunan and assess predictors of successful SC. Methods: The participants in this study were smokers who visited the SC clinic of Hunan Cancer Hospital from February 1, 2015 to September 30, 2018. Individuals who received individual counseling and assessment from the SC clinic staff and were willing to quit smoking were eligible for inclusion. Those with critical illness or cancer were excluded. Application of smoking cessation clinic registration form (unified by Chinese Center for Disease Control and Prevention) was used to assess participants at the consultation. Follow-ups and counseling were performed over telephone at one week, one month, and three months after the initial cessation consultation or in times of need. Successful SC was checked for at three months after the start of SC. Results: A total of 328 smokers (mean age 45.67 ± 12.38 years) had participated. The abstinence rate at three months was 28.4%. Multivariate binary regression analysis revealed significant independent predictors to be the total numbers of SC follow up sessions, previous SC attempts, and participants’ decision on when to quit smoking (The relative to quit immediately group, quit within 30 days, quit after 30 days, and undecided quit were less likely to succeed in quitting. while quit within seven days had no statistical significance.